A Comparative Study of VLF Transmitter Signal Measurements and Simulations during Two Solar Eclipse Events - Wen Cheng; Wei Xu; Xudong Gu; Shiwei Wang; Qingshan Wang; Binbin Ni; Zilong Lu; Binxiao Xiao; Xiaoyu Meng (Remote Sensing, 2023)
To monitor the Very-Low-Frequency (VLF) environment, a VLF detection system has been installed in Suizhou, China, a location with the longitude almost identical to that of the NWC transmitter in Australia. In the years 2019 and 2020, two solar eclipses crossed the NWC–Suizhou path at different locations. Each solar eclipse event represents a naturally occurring controlled experiment, but these two events are unique in that similar levels of electron density variation occurred at different locations along the VLF propagation path. Therefore, we conducted a comparative study using the VLF measurements during these two eclipses. Previous studies mostly estimated a pair of the reflection height (h′) and sharpness parameter (β) using the Long Wavelength Propagation Capability code, whereas, in this study, we use the VLF amplitude and phase as constraints in order to find the electron density change that best explains the VLF measurements. The eclipse measurements could be best explained if the path-averaged β value was 0.56 and 0.62 km−1 for the 2019 and 2020 eclipse, respectively. The VLF reflection height increased from 71.5 to 73.3 km for the 2019 eclipse and from 71.1 to 72.8 km for the 2020 eclipse. The best-fit β values were consistent with the Faraday International Reference Ionosphere model and statistical studies, and the h′ change was also consistent with previous studies and theoretical calculations. Moreover, present results suggested that VLF signals collected by a single receiver were not sensitive to where the electron density change occurs along the propagation path but reflected the average path condition. Therefore, a network of VLF receivers is required in order to monitor in real time the spatial extent of the space weather events that disturb the lower ionosphere.